Antiseptic Soap Making Training to Increase Economic Independence at the Aisyiyah Prambatan Kidul Kudus Orphanage - Puspitasari, Indah; Mundriyastutik, Yayuk; Cholifah, Noor; Nisak, Ana Zumrotun (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
The coaching activities at the Aisyiyah Kudus Orphanage run regularly every day. To meet the financing of this activity, the Aisyiyah Kudus Orphanage only relies on aid funds from donors. Therefore, the problem of meeting living expenses and limited education costs are the main problems faced by the management of the Aisyiyah Kudus Orphanage, so there needs to be an effort so that the continuity of activities at the Aisyiyah Kudus Orphanage continues to run well. The business in question is a business that is able to provide optimal economic added value and help increase the economic independence of the institution, namely the manufacture of herbal antiseptic soap derived from pletekan leaves. Pletekan leaf is a wild plant that grows a lot on the roadside and around the yard. The content of pletekan leaves is that it contains alkaloids, flavonoids, saponins and phenols. Pletekan leaves can be used to make antiseptic soap. The purpose of this community service is to increase the knowledge and skills of the children and administrators of the 'Aisyiyah Kudus Orphanage in utilizing the pletekan leaf plant as an antiseptic herbal soap product and to increase the ability in marketing and sales strategies so as to be able to increase the economy independently at the 'Aisyiyah Orphanage. Holy. This Community Service activity was initiated by coordinating with the leadership of the Aisyiyah Orphanage before the activity was carried out. In this service activity, three stages were carried out, namely opening, health seminars and training on the practice of making antiseptic soap, and finally a seminar on managing distribution permits and the practice of creating marketplace accounts for sales.